Resin composition and method for producing same

The resin composition with a copolymer of aromatic and cycloaliphatic monomers addresses the limitations of liquid rubber resins by enhancing dielectric properties and peeling strength, improving substrate performance.

JP7623451B2Active Publication Date: 2025-01-28NANYA PLASTICS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023163986
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-31
Filing Date
2023-09-26
Publication Date
2025-01-28
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

Existing liquid rubber resins used for high-frequency transmission substrates have low glass transition temperature, poor reactivity, high melt viscosity, and low peeling strength, which hinder their effectiveness in maintaining good dielectric characteristics.

Method used

A resin composition incorporating a copolymer with an aromatic monomer and a cycloaliphatic monomer, designed with a specific molecular weight and monomer ratio, is used to enhance dielectric properties and peeling strength.

Benefits of technology

The resin composition achieves improved dielectric characteristics, increased glass transition temperature, and enhanced peeling strength, resulting in better performance of substrates such as circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623451000001
    Figure 0007623451000001
  • Figure 0007623451000002
    Figure 0007623451000002
  • Figure 0007623451000003
    Figure 0007623451000003
Patent Text Reader

Abstract

To provide a resin composition from which a substrate having good low dielectric characteristics is manufactured, and that a glass transition temperature and peeling strength simultaneously increase, and a method for producing the same.SOLUTION: A resin composition contains a copolymer. The copolymer contains divinyl benzene (x), an aromatic monomer (y), and an alicyclic monomer (z), x:y:z is 1:1 to 10:0.1 to 5, the molecular weight of the copolymer is 2,000 to 5,000, the aromatic monomer contains a styrene monomer, a ratio of the styrene monomer to the copolymer is 20% to 90%, and a ratio of the alicyclic monomer to the copolymer is 1% to 30%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a method for producing the same. [Background technology]

[0002] In order for a substrate to have high frequency transmission capability, it is generally required to exhibit low dielectric properties such as low dielectric constant (Dk) and low dielectric loss tangent (Df). In order to satisfy these property requirements, liquid rubber resin with excellent insulating properties is generally used.

[0003] However, since liquid rubber resins are thermosetting resins with few reactive groups, they are prone to defects such as a low glass transition temperature (Tg), poor reactivity, poor processability, high melt viscosity, low peel strength, etc. Therefore, it is an important task to provide a resin composition that can improve these defects while maintaining the good low dielectric properties of the substrate. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a resin composition which allows the produced substrate to have good low dielectric properties while at the same time increasing the glass transition temperature and peel strength. [Means for solving the problem]

[0005] The resin composition of the present invention includes a copolymer. The copolymer includes an aromatic monomer and an alicyclic monomer. The molecular weight of the copolymer is 2000 to 5000, and the ratio of the alicyclic monomer to the copolymer is 1% to 30%.

[0006] In one embodiment of the present invention, the copolymer contains vinyl groups, and the proportion of vinyl groups in the copolymer is 10% to 40%.

[0007] In one embodiment of the present invention, the aromatic monomer includes a styrene monomer, and the ratio of the styrene monomer to the copolymer is 20% to 90%.

[0008] In one embodiment of the present invention, the copolymer has the general chemical structure: [ka] In the formula, R1 is as follows: [ka] R2 is selected from at least one of the following formulas: [ka] R3 is selected from at least one of the following formulas: [ka] And x:y:z is 1:1 to 10:0.1 to 5.

[0009] The method for producing a resin composition of the present invention includes at least the following steps: A step of producing a copolymer, the step including a step of dissolving at least a Lewis acid catalyst, an aromatic compound, and an alicyclic compound in a solvent to form a first solution, and a step of neutralizing the first solution using an alkaline solution. The copolymer includes an aromatic monomer and an alicyclic monomer, and has a molecular weight of 2000 to 5000. The ratio of the alicyclic monomer to the copolymer is 1% to 30%.

[0010] In one embodiment of the present invention, the copolymer has the general chemical structure: [ka] In the formula, R1 is derived from at least one of divinylbenzene and butadiene. R2 is derived from at least one of styrene, 4-vinylbiphenyl, and 2-vinylnaphthalene. R3 is derived from at least one of acenaphthalene, cyclopentadiene, cyclobutadiene, norbornene, and dicyclopentadiene. x:y:z is 1:1 to 10:0.1 to 5.

[0011] In one embodiment of the present invention, the Lewis acid catalyst comprises SnCl4·H2O or BF3.Oet3.

[0012] In one embodiment of the invention, the solvent comprises toluene or dimethylformamide.

[0013] In one embodiment of the present invention, the alkaline solution comprises an aqueous NaHCO3 solution.

[0014] In one embodiment of the present invention, the reaction temperature of the neutralization is 70° C. or higher. Effect of the Invention

[0015] From the above, the resin composition of the present invention introduces a copolymer containing an aromatic monomer and an alicyclic monomer, and by designing according to the ratio of the alicyclic monomer, the copolymer contains a non-polar skeleton structure. Therefore, the substrate (circuit board, copper foil substrate, etc.) produced has good low dielectric properties, and at the same time, the glass transition temperature and peel strength are improved.

[0016] In order to make the above mentioned features and advantages of the present invention more comprehensible, the following specific embodiments are described in detail in conjunction with the accompanying drawings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] In the following detailed description, for purposes of explanation and not limitation, example embodiments disclosing specific details are set forth to provide a thorough understanding of various principles of the invention. Moreover, descriptions of well-known devices, methods and materials may be omitted so as not to obscure the description of various principles of the invention.

[0018] In this specification, ranges expressed as "a certain value to another value" are schematic expressions to avoid listing all the values ​​within the range in the specification, and therefore, the description of a specific numerical range is intended to encompass any numerical range, including any numerical value and any smaller numerical range explicitly described in the specification.

[0019] Unless otherwise specified, the term "between" as used herein to define a range of values ​​is intended to cover the range equal to and between the specified endpoints. For example, a size range between a first value and a second value can cover the first value, the second value, and any value between the first value and the second value.

[0020] In the present invention, non-limiting terms (eg, can or other similar terms) refer to unnecessary or optional implementations, inclusions, additions, or presences.

[0021] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art. Furthermore, it should be noted that technical terms (such as terms defined in commonly used dictionaries) should be interpreted consistently in the relevant technical context and should not be interpreted in an idealized or overly formal sense unless the term is clearly defined as such.

[0022] In this embodiment, the resin composition contains a copolymer of an aromatic monomer and an alicyclic monomer. The molecular weight of the copolymer is 2000 to 5000. The ratio of the alicyclic monomer to the copolymer is 1% to 30%. In this way, the resin composition of the present invention introduces a copolymer containing an aromatic monomer and an alicyclic monomer, and by designing according to the ratio of the alicyclic monomer, the copolymer contains a non-polar skeleton structure. Therefore, the substrate (circuit board, copper foil substrate, etc.) produced has good low dielectric properties, and at the same time, the glass transition temperature and peel strength are improved. Here, the molecular weight is, for example, a number average molecular weight.

[0023] Furthermore, since the non-polar skeleton structure is not easily polarized, the dielectric constant (Dk, 10kz) and dielectric dissipation factor (Df, 10kz) of the copper foil substrate produced are 3.1 and less than 0.0014. Therefore, the dielectric properties are significantly reduced, and the glass transition temperature exceeds 220°C, so that the copper foil substrate has an excellent glass transition temperature. Furthermore, since the copolymer has reactive double bonds, it is possible to improve reactivity, heat resistance, chemical resistance, cold resistance, and low-temperature flexibility (improved brittleness, improved toughness) and improve solvent solubility (acetone solubility 40%, etc.) by intermolecular crosslinking, but the present invention is not limited thereto.

[0024] In some embodiments, the copolymer contains vinyl groups. The ratio of vinyl groups to the copolymer is 10% to 40%. For example, the aromatic monomer contains styrene monomer. The ratio of styrene monomer to the copolymer is 20% to 90%, but the present invention is not limited thereto.

[0025] In some embodiments, the general chemical structure of the copolymer is as follows: [ka]

[0026] Furthermore, R1 is as follows: [ka] R2 is selected from any of the following formulas: [ka] R3 is selected from any of the following formulas: [ka]

[0027] Here, specific examples of the copolymer include, but are not limited to, one of the above combinations. As long as the copolymer has a non-polar skeleton structure, it is within the scope of protection of the present invention.

[0028] Further, x:y:z (molar ratio) is 1:1 to 10:0.1 to 5. For example, x:y:z is 1:1:0.1, x:y:z is 1:10:0.1, x:y:z is 1:1:5, x:y:z is 1:5:1, or other preferred ratios within the above range.

[0029] In some embodiments, R1 is derived from divinylbenzene (DVB) or butadiene. R2 is derived from one of styrene, 4-vinylbiphenyl, and 2-vinylnaphthalene. R3 is derived from one of acenaphthalene, cyclopentadiene, cyclobutadiene, norbornene, and dicyclopentadiene (DCPD). Furthermore, the above-mentioned raw materials are dissolved in a solvent using a Lewis acid catalyst, and the raw materials are reacted for 6 to 8 hours under an environment of 0°C to 100°C, and then neutralized with an alkaline aqueous solution to form a copolymer. The manufacturing process will be described in more detail below. The Lewis acid catalyst is, for example, SnCl 4· 5H2O or BF3.Oet 3, The solvent is, for example, toluene or dimethylformamide (DMF). The alkaline aqueous solution is, for example, an aqueous NaHCO3 solution. However, the present invention is not limited thereto. In other embodiments, the Lewis acid catalyst is, for example, a metal fluoride (e.g., SnF4, WF6, HfF4, ZrF4) or complex (e.g., WCl6, AlCl3, SbCl3, FeBr3, FeCl3, TiCl4, ZnCl2, NbCl5, CF3SO3H, TiCl3-Al(C2H5)3, TiCl4 / LiAlH4, TiCl4 / MAO, ZrCl4 / MAO, TiCl3 / MAO, VCl4 / MAO, CrCl3 / MAO, TiCl4 / MgCl2, TiCl4 / NdCl3, TiCl4 / VCl3, TiCl4 / EtAlCl2, RuCl2(=CHPh)(PCy3)2, RuCl2(=CHPh)(PCy3)(L), RuCl2(=CHCH=CH2)(PCy3)(L)).

[0030] It should be noted that the resin containing the copolymer may be a modified liquid rubber resin, which is a resin composition consisting of, for example, polyphenylene ether resin (SA9000, OPE-2st, etc.), crosslinker (TAIC, etc.), maleimide, resin (MIR-3000, etc.), flame retardant (PQ60, etc.) and / or filler (SiO2, etc.), etc. Furthermore, the aromatic ratio, alicyclic ratio, and styrene monomer ratio may be molar ratios, but the present invention is not limited thereto.

[0031] The effects of the present invention will be described below with reference to examples and comparative examples, but the scope of the present invention is not limited to these examples.

[0032] The copper foil substrates produced in the respective Examples and Comparative Examples were evaluated according to the following methods.

[0033] Glass transition temperature (Tg): Measured using a dynamic mechanical analyzer (DMA).

[0034] Relative dielectric constant (10 GHz): The relative dielectric constant at a frequency of 10 GHz was measured using a dielectric constant analyzer.

[0035] Dielectric loss (10 GHz): The dielectric loss at a frequency of 10 GHz was measured using a dielectric constant analyzer.

[0036] Peel strength: The peel strength of the metal substrate was tested according to the test method of IPC-TM-650-2.4.8.

[0037] Heat resistance: A metal substrate was heated in a pressure cooker at 120°C and 2 atmospheres for 120 minutes, then immersed in a soldering furnace at 288°C and the time required for explosion was recorded. If the explosion time was 10 minutes or longer, it was marked as "OK", and if the explosion time was less than 10 minutes, it was marked as "NG".

[0038] <Copolymer 1~Copolymer 6>

[0039] According to the ratio of raw materials R1, R2 and R3 (alkenyl group compound, aromatic compound, alicyclic compound, corresponding to the above general chemical structure formula) shown in Table 1, raw materials R1, R2 and R3 were dissolved in 24 milliliters of the solvent shown in Table 1 together with 0.2 grams of Lewis acid catalyst shown in Table 1 to form a first solution. In addition, several related reaction conditions are shown in Table 1. The first solution was obtained by using a round-bottom reaction flask equipped with a stirring mixer and introducing nitrogen into the reaction flask to remove air and moisture. The first solution was mixed uniformly at 300 rpm. Then, the first solution was neutralized using an alkaline aqueous solution (NaHCO3 aqueous solution with a concentration of 8%). When the reaction temperature of the first solution is 70 ° C or higher, the solid in the first solution dissolves into a transparent liquid, and then continues to react at the same temperature for 2 hours, so that the transparent solution becomes a viscous solution before being neutralized. Then, the solution was filtered and vacuum dried to obtain copolymers 1 to 6.

[0040] [Table 1]

[0041] <Examples 1 to 6 and Comparative Examples 1 to 6>

[0042] According to the blending ratio of each component shown in Table 2, the components were mixed using toluene to form a varnish of a thermosetting resin composition. This varnish was impregnated into Nanya glass fiber cloth (manufactured by Nanya Plastics Co., Ltd., cloth model number: 1078) at room temperature. It was then dried at 130°C (impregnation machine) for several minutes to obtain a prepreg with a resin content of 60 wt%. Finally, four prepregs were laminated between two sheets of copper foil with a thickness of 35 μm, and the laminate was pressed at a pressure of 25 kg / cm. 2 The temperature was then kept constant at 85°C for 20 minutes. Thereafter, the temperature was increased to 210°C at a rate of 3°C / min, and the temperature was then kept constant for 120 minutes. Next, the temperature was gradually cooled to 130°C to obtain copper foil substrates having a thickness of 0.5 mm for Examples 1 to 6 and Comparative Examples 1 to 6. Here, B-1000, B-2000 (Nippon Soda Co., Ltd.), and RI 257 (CRAY VALLEY) are commercially available unmodified liquid rubber resins.

[0043] The produced copper foil substrates were tested for relevant properties, and the results are shown in Table 2. Comparing the results of Examples 1 to 6 and Comparative Examples 1 to 6 in Table 2, the following conclusions can be drawn: Compared with Comparative Examples 1 to 6, the copper foil substrates of Examples 1 to 6 have similar other properties (dielectric properties, heat resistance, etc.), but have significantly improved glass transition temperatures and peel strengths.

[0044] [Table 2]

[0045] In summary, the resin composition of the present invention introduces a copolymer containing an aromatic monomer and an alicyclic monomer, and by designing according to the ratio of the alicyclic monomer, the copolymer contains a non-polar skeleton structure, so that the substrate (circuit board, copper foil substrate, etc.) produced has good low dielectric properties and at the same time, the glass transition temperature and peel strength are improved.

[0046] Although the present invention has been disclosed by the above embodiments, these embodiments do not limit the present invention, and those skilled in the art can make some changes and modifications without departing from the spirit and scope of the present invention. The protection scope of the present invention is defined by the appended claims. [Industrial Applicability]

[0047] The resin composition of the present invention and a substrate produced therefrom can be used to improve glass transition temperature and peel strength.

Claims

1. A resin composition comprising a copolymer having a number average molecular weight of 2000 to 5000, the copolymer comprising an aromatic monomer and an alicyclic monomer, the copolymer comprising the aromatic monomer and an alicyclic monomer being 1% to 30%, and the copolymer having the following general chemical structure: 【Chemistry 1】 During the ceremony, R 1 is derived from butadiene. R 2 is derived from at least one of 4-vinylbiphenyl, 2-vinylnaphthalene. R 3 is derived from at least one of acenaphthalene, cyclopentadiene, cyclobutadiene, dicyclopentadiene. The molar ratio of x:y:z is 1:1-10:0.1-5.

2. The resin composition according to claim 1, wherein the copolymer contains vinyl groups, and the ratio of the vinyl groups to the copolymer is 10% to 40%.

3. dissolving at least a Lewis acid catalyst, an aromatic compound, and an alicyclic compound in a solvent to form a first solution; neutralizing the first solution using an alkaline solution; The copolymer includes an aromatic monomer and an alicyclic monomer, the number average molecular weight of the copolymer is 2000 to 5000, the ratio of the alicyclic monomer to the copolymer is 1% to 30%, and the copolymer has the following general chemical structural formula: 【Chemistry 2】 During the ceremony, R 1 is derived from butadiene. R 2 is derived from at least one of 4-vinylbiphenyl, 2-vinylnaphthalene. R 3 is derived from at least one of acenaphthalene, cyclopentadiene, cyclobutadiene, dicyclopentadiene. The molar ratio of x:y:z is 1:1-10:0.1-5.

4. The Lewis acid catalyst is SnCl 4 ・H 2 O or BF 3 .Oet 3 The method for producing the resin composition according to claim 3, comprising:

5. The method for producing a resin composition according to claim 3 , wherein the solvent includes toluene or dimethylformamide.

6. The alkaline solution is NaHCO 3 The method for producing the resin composition according to claim 3, comprising an aqueous solution.

7. The method for producing a resin composition according to claim 3, wherein the neutralization reaction is carried out at a reaction temperature of 70°C or higher.

Citation Information

Patent Citations

  • Conjugated diene-based elastomer, method for producing the same, rubber composition, rubber elastic body and tire

    JP2012251118A

  • Soluble polyfunctional vinyl aromatic copolymer, method for producing the same, curable resin composition, and cured product of the same

    JP2018039995A

  • Thermosetting resin, cured product of the same and thermosetting composition

    JP2024138812A

  • Curable resin composition, prepreg, metal-clad laminate, and printed wiring board

    WO2021166649A1